Ecologia trófica e ecomorfologia de peixes em um trecho do Alto Rio São Francisco impactado pela transposição do Rio Piumhi, com ênfase nas espécies Pimelodus fur Lütken, 1874 e Leporinus reinhardti Lütken, 1875 - Stefani, Patrícia Monte (Universidade Federal de São Carlos, 2010)
Studies on the feeding of fishes provide relevant information for understanding the mechanisms allowing the coexistence and exploitation of resources by several species of fishes and also by other components of the aquatic communities.. The objective of the present study was to analyze in detail the feeding habits and the ecomorphology of the fish species Pimelodus fur and Leporinus reinhardti as well as to preliminarily characterize the fedding habits and describe the morphological characteristics of other nine species of fish occurring in a stretch of the Upper São Francisco River Basin. Fishes were sampled in four periods: December 2006 and 2008 (rainy periods) and April 2007 and June 2008 (dry periods) using with gillnets, seine nets and sieve. The results on the feeding ecology of P.fur revealed that this species belong to the trophic gulid of the insectivores, since insects represent between 74.0% and 79.0% of its diet. There were seasonal changes in the diet of P. fur, with food items essentially authochtonous, as aquatic insects larvae being consumed in the dry periods and insects from terrestrial sources, as Araneae and Hymenoptera being added to its diet during the rainy periods, in both São Francisco River and its tributary Piumhi River. In these rivers P. fur displayed high trophic specialization, being a specialist in consuming aquatic insects. It was also observed great overlap in the food items consumed by the different size classes of P. population sampled in both rivers. L. reinhardti had intense feeding activity in both seasons dry and rainy periods. This species belong to the trophic guild of herbivores, being its diet composed mainly by plant material. The feeding spectrum of L. reinhardti is wider in São Francisco River than in the Piumhi River, what can be a consequence of the fact that the gallery forest in the São Francisco River is better preserved in this region than that of the Piumhi River. There were seasonal changes in the diet of L. reinhardt, with some food items as Trichoptera and Hymenoptera only being consumed in the rainy periods. There was no significant change in the diet of L. reinhardti along its development, with preference by plant material in all size classes. L. reinhardti is a feeding specialist with narrow niche breath. There was no feeding niche overlap between P. fur and L. reinhardti in any seasonal period or river stretch studied. Although feeding activity of both P. fur and L. reinhardti was intense during all periods analyzed, the narrow feeding niche breath and the large diet overlap among the size classes within each species population indicate that food sources are abundant in this part of the Upper São Francisco River basin. Regarding the morphological characteristics there was also trophic structuring of the species studied in Piumhi and São Francisco Rivers, with segregation between the body shape of the specialists (insectivores and piscivores) and the more generalist feeders (omnivores and herbivores).
Trophic ecology and ecomorphology of fishes in a stretch of the the Upper São Francisco River basin, impacted by the transposition of Piumhi River, with emphasis on the species Pimelodus fur Lütken, 1874 and Leporinus reinhardti, Lütken, 1875
Keywords: Cadeias alimentares (Ecologia); Guildas tróficas; Peixes - alimentação; Ecomorfologia; Bacia do São Francisco; Fish feeding; Trophic guilds; Ecomorphology; São Francisco basin; CIENCIAS BIOLOGICAS::ECOLOGIA